Decoding the effect of time interval between hCG and IUI and sperm preparation and IUI - Agrawal, Smriti; Das, Vinita; ., Karuna; Agarwal, Anjoo; Pandey, Amita; ., Namrata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The study was aimed to assess the difference in IUI outcome depending on the interval between hCG trigger and IUI and sperm preparation and IUI. Methods: The study was conducted in the Department of Obstetrics and Gynecology in Infertility unit at King George’s Medical University, Lucknow from January-December 2016. All the women eligible for IUI were included in the study. Once the follicle attained size of 17-18 mm, IUI was planned 36-48 hours after Inj. hCG 10,000 IU im. Semen processing was done in laboratory and time noted between sperm preparation and IUI. Outcome was confirmation of pregnancy by urine test. Cases were women in whom IUI was done 36-40 hours after hCG as against controls (>40 hours). Interval between sperm preparation and IUI was <30 minutes in cases and ≥30 minutes in controls. Results: A total of 624 cycles were included in the study. Clomiphene was used in 582/624 cycles (93.3%) gonadotropins used in 42/624 cycles (2.7%). There was a total of 23 conceptions in study (3.7%). Of these 8/98 (8.2%) were seen when the interval between ovulation trigger and IUI was 36-40 hours and 15/526 in cycles (2.9%) when the interval was more than 40 hours (p=0.023; OR-3.028 95% CI -1.247-7.352). Of a total of 23 conceptions in the study, 18/324 conceptions were seen when IUI was done within 30 minutes of sperm preparation as compared to 5/300 when interval was more than 30 minutes (p=0.01). Conclusions: IUI with ovarian stimulation is a simple and effective procedure and its outcome can be maximized keeping in consideration the availability of gametes. IUI performed within 36-40 hours of hCG trigger and within 30 minutes of sperm preparation can increase conception rates.